Concurrent Design Of Green Composites - Mansor, Muhd Ridzuan; Akop, Mohd Zaid; Sapuan, S.M.; Mohd Tahir, Musthafah; Salim, Mohd Azli; Shaharuzaman, Mohd Adrinata (IGI Global, 2006)
This chapter presents the overview of concurrent design process of green composite products with special focus on conceptual design stage of natural fiber composites product development. Design of green composites product especially during the early product development stage requires three main aspects in product design which are materials, design and manufacturing process to satisfy lower cost, high quality and fast development time requirements in order to ensure successful product launch into the market. In this chapter, the concurrent design process of green composite products are discussed involving several main stages in product development such as green composite materials selection for both natural fiber and matrix constituents,conceptual design development and concept design selection of green composite products, and green composites manufacturing process selection. In addition, discussion on life cycle assessment of green composites is also included in order to provide further insight of the sustainability design requirements to the overall product development process.